2017
DOI: 10.1007/978-3-319-55982-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biogeography of the High Mountain Systems of Europe: An Overview

Abstract: The biogeography of alpine and arctic-alpine species is complex, much more complex than thought until relatively recently. Alpine species survived glacial periods mostly within refugia in close proximity to the mountains where they are found today. One mountain range can be colonised from several glacial refugia, while one refugium can be the source of colonisation of more than one mountain range. The zonal distributions in the glacial cold steppes are only of importance for arctic-alpine species. Their arctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…A recent study on leaf morphology in S. retusa agg. (Kosiński et al ) confirmed that S. retusa s.l. populations in the Tatra Mountains (the western Carpathians) had leaf length and width twice as long as the average found for the rest of the populations of S. retusa s.l., which corresponds to the description of S. kitaibeliana , and justify from a morphological standpoint distinguishing them as a separate taxon.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…A recent study on leaf morphology in S. retusa agg. (Kosiński et al ) confirmed that S. retusa s.l. populations in the Tatra Mountains (the western Carpathians) had leaf length and width twice as long as the average found for the rest of the populations of S. retusa s.l., which corresponds to the description of S. kitaibeliana , and justify from a morphological standpoint distinguishing them as a separate taxon.…”
Section: Introductionmentioning
confidence: 88%
“…These taxa are different in terms of ecology: S. serpillifolia is calcicolous, S. kitaibeliana is acidophilous, while S. retusa s.s. has a broader, intermediate tolerance (Pawłowski , Skvortsov , Hörandl et al 2002). The morphological differences among them are mainly quantitative: leaves of S. serpillifolia are on average half the size of leaves of S. retusa s.s. (Rechinger , Kosiński et al ), while leaves of S. kitaibeliana are approximately twice as long and broad as those of S. retusa s.s. (Supplementary material Appendix 1 Fig. A1) (Dostál , Rechinger , Kosiński et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They went through contrasting climatic conditions such as those corresponding to the Quaternary succession of cold and temperate periods. In this sense, some ancient plant and animal endemics have apparently remained from Pliocene onwards roughly within their present range (Schmitt 2017). Interestingly, most of these species, called paleoendemic, correspond to more or less isolated tips in phylogenetic trees and nowadays are found in conservative habitats (Garcia et al 2012) and are focus of conservation biology research (Segarra-Moragues and Catalan 2010).…”
Section: Persistence Versus Migrationmentioning
confidence: 99%
“…Many mountains have been glaciated and deglaciated several times. Fragmentation and refugia during harsh periods explain the current distribution of many species and biogeographical paradoxes among sister species (Schmitt 2017). Do we have the knowledge and tools to identify potential refugia within nature reserves (Gavin et al 2014)?…”
Section: Conservation Versus Stewardship (Franciscans Vs Benedictines)mentioning
confidence: 99%